Dual Therapies Containing an Antibiotic Plus a Proton Pump Inhibitor or Vonoprazan for Helicobacter pylori Infection: A Systematic Review - Chih-An Shih; Deng-Chyang Wu; Chang-Bih Shie; Ping-I Hsu (Microorganisms)
Due to the increasing prevalence of antimicrobial resistance, the efficacy of standard triple therapy for Helicobacter pylori (H. pylori) infection has declined, with eradication rates now falling below 80% in most countries. Although bismuth quadruple therapy and concomitant therapy are advised in regions with high clarithromycin resistance, these treatments commonly cause frequent adverse events and require the use of two or three antibiotics. This review article evaluates the effectiveness of 14-day mono-antibiotic therapies for H. pylori infection through randomized controlled trials conducted from 1 October 2014 to 1 October 2024. The pooled eradication rates for 14-day high-dose amoxicillin/proton pump inhibitor (PPI) dual therapies were 86.1% (3335/3875; 95% confidence interval (CI): 85.1–87.2%) by intention-to-treat (ITT) analysis and 87.3% (3232/3702; 95% CI: 86.2–88.4%) by per-protocol (PP) analysis. For 14-day high-dose amoxicillin/vonoprazan dual therapies, the rates were 87.4% (1085/1241; 95% CI: 85.5–89.2%) by ITT and 93.0% (1044/1124; 95% CI: 91.5–94.5%) by PP. In the penicillin-allergic population, 14-day tetracycline/vonoprazan dual therapy showed eradication rates of 92.0% (138/150) by ITT and 95.1% (135/142) by PP. In conclusion, 14-day tetracycline/vonoprazan dual therapy presents an effective option for eradicating H. pylori in patients allergic to penicillin. For those without a penicillin allergy, first-line treatments can include 14-day mono-antibiotic regimens, such as high-dose amoxicillin/PPI dual, high-dose amoxicillin/vonoprazan dual, and tetracycline/vonoprazan dual therapies.